2016
DOI: 10.1007/s00128-016-1833-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Bromothalonil and Flutolanil on Multiple Developmental Stages in Zebrafish

Abstract: In this study, we applied various developmental stages of zebrafish to address the potential environmental risk and aquatic toxicity of bromothalonil and flutolanil. This results demonstrated that the acute toxicity of bromothalonil to the three phases of zebrafish were 4.34 (embryo) < 3.27 (12 h old larvae) < 2.52 mg/L (adult fish) and that of flutolanil were 5.47 (embryo) < 4.09 (72 h old larvae) < 3.91 (12 h old larvae) < 2.70 mg/L (adult). Sublethal effects induced by both bromothalonil and flutolanil on z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The results of the present study suggest that triclosan exposure negatively affects both the embryonic and the early larval stage in Japanese medaka, with a particularly steep increase in mortality soon after hatching, which is consistent with previous reports of delayed mortality in zebrafish exposed to the dioxin‐like pollutant PCB‐126 (3,3′,4,4′,5‐pentachlorobiphenyl) (Di Paolo et al, ) or to chlorinated anilines (Horie, Yamagishi, Koshio, et al, ). Mu et al () and Yang et al () have also reported that the sensitivities of zebrafish to the acute toxic effects of environmental chemicals are different before and after hatching. Together, these reports suggest that the lethal effects of environmental chemicals in fish should be assessed separately in the embryonic and larval stages.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study suggest that triclosan exposure negatively affects both the embryonic and the early larval stage in Japanese medaka, with a particularly steep increase in mortality soon after hatching, which is consistent with previous reports of delayed mortality in zebrafish exposed to the dioxin‐like pollutant PCB‐126 (3,3′,4,4′,5‐pentachlorobiphenyl) (Di Paolo et al, ) or to chlorinated anilines (Horie, Yamagishi, Koshio, et al, ). Mu et al () and Yang et al () have also reported that the sensitivities of zebrafish to the acute toxic effects of environmental chemicals are different before and after hatching. Together, these reports suggest that the lethal effects of environmental chemicals in fish should be assessed separately in the embryonic and larval stages.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that it is necessary to investigate not only the embryo stage (when various organs and tissue are formed) but also the influence after hatching (when all organs and biological functions are working normally), to evaluate accurately the influence of diclofenac. In addition, it has been previously demonstrated that the embryonic and larval stages of zebrafish have different sensitivities to toxic chemicals (Horie, Yamagishi, Koshio, et al, ; Horie, Yamagishi, Takahashi, et al, ; Mu et al, ; Yang et al, ). Furthermore, we revealed that triclosan exposure also negatively affects with a particularly steep increase in mortality soon after hatching in O. latipes (Horie, Yamagishi, Takahashi, Shintaku, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that the embryonic and larval stages of zebrafish have different sensitivities to toxic chemicals,i.e., a particularly steep increase in mortality after hatching (Horie, Yamagishi, Koshio, et al, ; Horie, Yamagishi, Takahashi, et al, ), possibly because the chorion blocks the transport of certain chemical compounds into eggs (Kim & Tanguay, ; Olivares, Field, Simonich, Tanguay, & Sierra‐Alvarez, ). Morphological abnormalities at the embryo stage have been shown to be induced by various chemicals in zebrafish, and these abnormalities can lead to delayed development or mortality (Almond & Trombetta, ; Bonventre, White, & Cooper, ; Di Paolo et al, ; Horie, Yamagishi, Koshio, et al, ; Horie, Yamagishi, Takahashi, et al, ; Melo et al, ; Mu et al, ; Vergauwen et al, ; Yang et al, ). This suggests that morphological abnormalities at the embryo stage may be suitable endpoints for predicting the lethal effects of environmental chemicals after hatching.…”
Section: Introductionmentioning
confidence: 99%
“…() and Yang et al . () have reported that the sensitivity of zebrafish to acute toxicity induced by environmental chemicals is different before and after hatching, and Kim and Tanguay () have reported that the chorion can block the transport of silver nanoparticles. Together, these results suggest that assessment of the lethal effects of environmental chemicals in fish should be conducted not only during the embryonic stage but also during the larval stage.…”
Section: Discussionmentioning
confidence: 99%
“…Ecotoxicological testing using fish embryos is a common means of clarifying the effects of environmental chemicals on aquatic organisms. Several toxicity tests have been published by the Organization for Economic Co-operation and Development (OECD) for the evaluation of the effects of environmental chemicals on aquatic organisms, including OECD TG 212 (Fish, Short-term Toxicity Test on Embryo and Sac-Fry Stages; OECD, 1998) and OECD TG 236 (Fish Embryo Acute Toxicity Test;OECD, 2013), which both use zebrafish (Danio rerio) embryos and have been shown to be useful for predicting the acute toxicity of environmental chemicals in fish (Belanger et al, 2013;Horie et al, 2017;Knoebel et al, 2012;Lammer et al, 2009;Yang et al, 2016). Although OECD TG 212 or OECD TG 236 can be used to investigate the lethal effects of environmental chemicals on the embryonic stages of zebrafish, only OECD TG 212 can be used to examine the effects in the sac-fry stage and to assess directly the sublethal effects of chemical exposure (Di Paolo et al, 2015;Horie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%